Efektivitas Konten Multimedia terhadap Calon Penyewa Kos di Tengah Mobilitas Penduduk - Nadya Satya Handayani; Sukma Evadini; Fatihatul Khoeroh; Risda Natalina Br Sirait; Reny Alisiyani Rahma; Ahmad Gibran; Febe Natali (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2026)
The increasing influx of migrants to major cities, driven by developments in the education and industrial sectors, has resulted in a growing demand for temporary accommodation, particularly boarding houses. Nevertheless, prospective tenants continue to encounter significant challenges in obtaining comprehensive and accurate information regarding available boarding houses. Fragmented information, insufficient visual representation of housing conditions, and limited promotional media constitute the primary obstacles that hinder the decision-making process. This study aims to design an Instagram-based digital promotional medium for boarding houses using the Design Thinking method, as well as to evaluate the effectiveness of the resulting medium. The findings indicate that prospective tenants exhibit a preference for promotional media that is informative, transparent, easily comprehensible, and capable of depicting housing conditions in a realistic manner. This study offers at least two contributions. First, from the perspective of prospective tenants, Instagram-based promotional media enables the presentation of boarding house information in a more structured and engaging format, thereby facilitating access to the information required for informed decision-making. Second, from the perspective of boarding house owners, this study demonstrates that the utilization of multimedia content through social media platforms constitutes an effective alternative strategy for promotion.